Pengaruh Konten Pemasaran Dan Citra Merek Terhadap Minat Beli Produk Uniqlo Di Instagram (Studi Pada Mahasiswa Manajemen Angkatan 2019 Universitas Buana Perjuangan Karawang) - Muhamad Rafsanjani; Citra Savitri; Syifa Pramudina Faddila (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Today, fashion is not only a necessity to cover the body, but also an expression of lifestyle and self-identity. The development of social media such as Instagram allows fashion information and inspiration to spread quickly. The purpose of this study was to determine the effect of marketing content and brand image on buying interest in Uniqlo products. This research uses a quantitative approach with a survey method. The analysis used is data validity test, classical assumption test, multiple linear regression analysis and hypothesis testing. The population in this study were Management Students Class of 2019, University of Buana Perjuangan Karawang. The sample consisted of 105 respondents who were taken based on purposive sampling technique with the criteria of having ever / intending to buy Uniqlo products on Instagram. Based on the results of the research that has been carried out, the results show that marketing content) and brand image have a positive and significant effect on buying interest in Uniqlo products on Instagram both partially and simultaneously.